1995
DOI: 10.1302/0301-620x.77b5.7559688
|View full text |Cite
|
Sign up to set email alerts
|

The pathology of frozen shoulder. A Dupuytren-like disease

Abstract: Of 935 consecutive patients referred with shoulder pain, 50 fitted the criteria for primary frozen shoulder. Twelve patients who failed to improve after conservative treatment and manipulation had excision of the coracohumeral ligament and the rotator interval of the capsule. The specimens were examined histologically, using special stains for collagen. Immunocytochemistry was performed with monoclonal antibodies against leucocyte common antigen (LCA, CD45) and a macrophage/synovial antigen (PGMI, CD68) to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
331
1
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(353 citation statements)
references
References 0 publications
11
331
1
10
Order By: Relevance
“…After the first description by Duplay in 1872 [1], it was better described by Codman [2] as "frozen shoulder"; however, it was only in 1945 that Neviaser [3] coined the term "adhesive capsulitis", after a cadaveric study, in which he found that the capsule was thickened and highly adherent to the humeral head while the bursa was unaffected, suggesting a chronic inflammatory condition. However, Lundberg et al [4] as well as Bunker et al [5] found no significant inflammatory cells and reported that the morphology of the contracted tissue was similar to that of Dupuytren's contracture. In 1975 Reeves et al [6] proposed three different phases to stage the disease: the painful phase, the frozen phase, and the thawing phase, with an overall estimated duration varying from 12 to 42 months.…”
Section: Introductionmentioning
confidence: 92%
“…After the first description by Duplay in 1872 [1], it was better described by Codman [2] as "frozen shoulder"; however, it was only in 1945 that Neviaser [3] coined the term "adhesive capsulitis", after a cadaveric study, in which he found that the capsule was thickened and highly adherent to the humeral head while the bursa was unaffected, suggesting a chronic inflammatory condition. However, Lundberg et al [4] as well as Bunker et al [5] found no significant inflammatory cells and reported that the morphology of the contracted tissue was similar to that of Dupuytren's contracture. In 1975 Reeves et al [6] proposed three different phases to stage the disease: the painful phase, the frozen phase, and the thawing phase, with an overall estimated duration varying from 12 to 42 months.…”
Section: Introductionmentioning
confidence: 92%
“…18,19,64,115 Numerous investigators report the visual presence of synovitis consistent with inflammation, 43,79,83,123 yet focal vascularity and synovial angiogenesis (increased papillary growth), rather than synovitis, are described by others. 18,50,124 In addition to confirmation of angiogenesis, frequent positive staining for nerve cells was found in patients with frozen shoulder. 42 However, if the synovial pathology is angiogenesis or synovitis, there is agreement that pain accompanies the change.…”
Section: Level 5 J Orthop Sportsmentioning
confidence: 99%
“…103 A greater than 50% reduction in passive external rotation or less than 30° of external rotation, when measured with the arm at the side, is a common finding in individuals with frozen shoulder. 8,15,18,24,39,78,96,100,107,119,121 Although authors of textbooks have described patients with frozen shoulder as having normal strength and painless resisted motions, 24 authors of recent studies, using handheld dynamometry, have revealed significant weakness of the shoulder internal rotators 53,59 and elevators 53,59,111 in these patients. The shoulder internal rotators were significantly weaker in patients with frozen shoulder compared to patients with rotator cuff tendinopathy; however, significant weakness of the external rotators and abductors was also found relative to the uninvolved side.…”
Section: Level 5 J Orthop Sportsmentioning
confidence: 99%
“…In the more common idiopathic primary frozen shoulder, it is characterised by an inflammatory contracture of the glenohumeral synovial capsule as well as other extra-articular softtissue structures such as the coracohumeral ligament, soft tissues of the rotator interval, the subscapularis muscle, and the subacromial bursae as a result of hyperplastic fibroplasia and excessive type III collagen secretion. 10 This reduces the available intra-articular volume thus limiting glenohumeral movement. Although generally considered self-limiting, it can lead to long-term disability and pain.…”
Section: Discussionmentioning
confidence: 99%